Integrating cold caesium atoms into optical waveguides - Da Ros, Elisa (2020)
This project focuses on a novel experimental method for interfacing cold atoms with optical waveguides. This relies on the introduction of cold atoms into microscopic laser-drilled holes that are perpendicular to the propagation axis of the waveguide. Direct interfacing of cold atoms with the guided mode of a waveguide is an attractive mechanism by which to create atom-photon interfaces, as the small mode area increases the interaction rate. Unlike many previous approaches, this technique can be applied in almost any existing waveguide system, including chip-based waveguide arrays and other complex environments. It therefore has great promise as a way of creating hybrid atom-photon quantum devices. Using this method, we demonstrate coupling between cold atoms and the light propagating in the core of an untapered single-mode optical fibre. This was achieved by laser-drilling a cylindrical, transverse hole (30 μm diameter) through the core of the fibre. Ensembles of cold caesium atoms can be tightly confined through an optical dipole trap within the microscopic void. Probe light, resonant with the Cs D2 line, is then coupled into the fibre. By measuring the transmitted optical power through the interface, it was determined that up to 87% of the probe power could be absorbed by the atoms. The corresponding optical depth per unit length of the atom cloud is over 700 cm^(-1), higher than any value reported to date for a comparable system. This will be a key parameter for the miniaturisation of atom-optical systems as well as for enhancing spatial resolution in sensing applications. The dependence of this absorption on several experimental parameters was also characterised and found to be in line with theoretical expectations. The atomic transition is not noticeably broadened by the presence of the fibre. We have also carried out numerical simulations of light transmission across wave-guide junctions of this type, proving that tailored hole geometries can enable enhanced optical transmission. The achievable degree of improvement is such that it is conceivable to place the void within an optical resonator, for example using laser-written Bragg gratings, and to achieve the strong coupling between the atoms and the guided light. Altogether this work demonstrates the potential of this technique to interface atoms with tightly confined light, allowing for integration in otherwise purely photonic circuits. In such environment the interaction between the atomic ensemble and the light can act as a node for the storage and processing of quantum information.